Wade Keyes, The Code of Alabama, 883 (1876), ch. 3, § 4111 (Act of Aug. 5, 1868, at 1) - (:unkn) unknown (General Publisher, 1868)
Prohibited the carrying of any rifle or “shot -gun walking cane.” Punishable by fine of $500-1000 and imprisonment of no less than 2 years.
--
Keywords: CARRY